Timing of troponin I measurement in pulmonary embolism. Issue 9 (20th April 2012) - Ferrari, Emile; Moceri, Pamela; Crouzet, Christophe; Doyen, Denis; Cerboni, Pierre
Abstract : Background: Troponin I (TnI) is an important prognostic marker and risk-stratification tool in patients with pulmonary embolism (PE). However, the best timing for this biomarker measurement is still unclear. Objective: To analyse the kinetics of TnI in patients hospitalised for PE in order to better ascertain the evolution of the biomarker in this disease. In particular, we attempted to determine which measurement is the most appropriate to assess the PE risk according to this biomarker's status. Design, setting, patients and main outcome measures: This was a prospective, single center, cohort study. TnI (Beckman Access method) was measured on admission, then every 8 h for 72 h in 200 stable patients hospitalised for PE in our cardiology department. Patients were classified into two groups: TnI−(negative) or TnI +. Results: Mean TnI peak occurred at H8: 0.67±0.55 ng/ml. TnI values then decreased quickly, but remained positive (>0.06 ng/ml) beyond the 72-h surveillance period. The TnI biological profile varied widely after admission. Of the patients TnI− on the first assessment, 15% were positive at the second measurement. Among patients hospitalised less than 24 h after the onset of symptoms, 30% were misclassified on admission. In all cases, the second assessment, eight hours after admission, gave the biomarker's true status. Conclusion: Our study clarifies the kinetics of TnI in PE and highlights the situations in which an early TnI can be false negative. Many misclassifications could be avoided by taking into account the value of this biomarker obtained at H8.